2010
DOI: 10.1002/nur.20393
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sedentary behavior in adolescents with type 1 diabetes

Abstract: The purpose of this study was to describe the associations between levels of physical activity measured by accelerometry and changes in fitness, body composition, lipids, and glucose control (i.e., glycosolated hemoglobin [A1C]) in a sample of 16 adolescents with type 1 diabetes participating in a personalized exercise program. More sedentary activity was associated with lower fitness and fat free mass and increased total cholesterol, low-density lipoprotein (LDL-c), and triglycerides (p < .05). Greater amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 35 publications
(49 reference statements)
4
69
0
9
Order By: Relevance
“…Another study classified the time dedicated to different intensities of physical activity performed by children and adolescents with T1D (23). Similar to the current study, the authors (23) observed that the time spent in sedentary activities (e.g.…”
Section: Discussionsupporting
confidence: 83%
“…Another study classified the time dedicated to different intensities of physical activity performed by children and adolescents with T1D (23). Similar to the current study, the authors (23) observed that the time spent in sedentary activities (e.g.…”
Section: Discussionsupporting
confidence: 83%
“…Studies of training program on group of adolescents with T1DM revealed that regular physical exercise significantly decrease HbA1c [8,18]. Other studies revealed similar significant results [4][5][6]9,19,20] which showed that improvement was associated with the frequency of physical activity [4,20].…”
Section: Discussionmentioning
confidence: 90%
“…Many studies of type 1 diabetes children or adolescent have demonstrated that exercise have a beneficial effect in type 1 diabetes. It lowers blood pressure [4], improves lipid profile [5,6], endurance capacity [7], body composition of fat to muscle mass ratio [8][9][10][11], physical fitness [7], insulin sensitivity [12], bone mineral density [11], vascular function [7], antioxidant capacity [13] and overall quality of the life [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Не было статистически Обучение и психосоциальные аспекты значимых различий в физической активности между па-циентами с разными режимами интенсивной инсулино-терапии (МИИ и ППИИ) [34]. В еще одном исследовании авторы Michaliszyn и Faulkner сообщают, что недостаток физической активности у подростков с СД1 приводит к повышению уровня свободных жирных кислот, общего холестерина, ЛПОНП, триглицеридов и HbA 1c [35].…”
Section: физическая активностьunclassified